2001
DOI: 10.4049/jimmunol.166.3.2090
|View full text |Cite
|
Sign up to set email alerts
|

Local Transgenic Expression of Granulocyte Macrophage-Colony Stimulating Factor Initiates Autoimmunity

Abstract: Mechanisms leading to breakdown of immunological tolerance and initiation of autoimmunity are poorly understood. Experimental autoimmune gastritis is a paradigm of organ-specific autoimmunity arising from a pathogenic autoimmune response to gastric H/K ATPase. The gastritis is accompanied by autoantibodies to the gastric H/K ATPase. The best characterized model of experimental autoimmune gastritis requires neonatal thymectomy. This procedure disrupts the immune repertoire, limiting its usefulness in understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 60 publications
0
44
1
2
Order By: Relevance
“…Our results demonstrate that GM-CSF expressed within the g -cells of the islets of Langerhans enhanced disease incidence in male NOD mice due to an increase in the availability of islet antigen. Recent studies have shown diverse functions of GM-CSF in the immune system [20,21,27,[32][33][34]. Our results suggest that in ins-GM-CSF mice, this height-ened response is mediated by increased numbers of APC infiltrating the pancreas as well as enhanced expression of B7-1 in CD11b + cells.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Our results demonstrate that GM-CSF expressed within the g -cells of the islets of Langerhans enhanced disease incidence in male NOD mice due to an increase in the availability of islet antigen. Recent studies have shown diverse functions of GM-CSF in the immune system [20,21,27,[32][33][34]. Our results suggest that in ins-GM-CSF mice, this height-ened response is mediated by increased numbers of APC infiltrating the pancreas as well as enhanced expression of B7-1 in CD11b + cells.…”
Section: Discussionmentioning
confidence: 56%
“…Transgenic expression of GM-CSF in the stomach of gastritis-susceptible BALB/cCrSlc mice results in development of autoimmune gastritis. In this latter model, the first stage of disease is associated with proliferation and activation of APC, which leads to migration of pathogenic CD4 + T cells into the gastric mucosa [20]. Recent work by our laboratory showed that the expression of GM-CSF in the pancreas of BALB/c mice greatly enhanced the recruitment and activation of APC within this organ [21].…”
Section: Introductionmentioning
confidence: 99%
“…47 The role of GM-CSF in immune regulation, however, is less clear. 48 Transgenic mice in which GM-CSF was expressed in the stomach epithelium developed gastritis, 49 whereas GM-CSF expression in the islets either exacerbated or inhibited diabetes, depending on the genetic background. 50,51 GM-CSF-deficient mice displayed reduced susceptibility to collagen-induced arthritis and experimental allergic encephalomyelitis, which correlated with the induction of weaker autoreactive T-cell responses, but preserved antibody reactions.…”
Section: Discussionmentioning
confidence: 99%
“…GM-CSF treatment in humans has not been implicated in the induction of autoimmune disease, but instead in the activation of pre-existing disease (52)(53)(54). In addition, studies in mouse models performed in genetically susceptible stains have implicated a role for GM-CSF in autoimmune disease severity (55,56). Together these studies argue that GM-CSF alone is insufficient to induce autoimmunity, but that in the presence of pre-existing autoimmune disease or predisposing factors, GM-CSF can aggravate disease symptoms.…”
Section: Discussionmentioning
confidence: 99%